Challenges and support factors in managing type 2 diabetes among pregnant women in Thailand: A convergent mixed-methods study - Ratchanok Phonyiam; Chiao-Hsin Teng; Catherine Sullivan; Aunchalee Palmquist; Eric Hodges; Yamnia Cortés; Marianne Baernholdt (Belitung Nursing Journal)
Background: Sociocultural and behavioral factors have a multifaceted impact on maternal health. In Thailand, cultural influences significantly shape behaviors of diabetes self-management in women. However, the experience of self-managing diabetes in pregnant women with preexisting Type 2 Diabetes Mellitus (T2DM) remains unclear.